DCE‐MRI texture analysis with tumor subregion partitioning for predicting Ki‐67 status of estrogen receptor‐positive breast cancers. Issue 1 (8th December 2017) - Fan, Ming; Cheng, Hu; Zhang, Peng; Gao, Xin; Zhang, Juan; Shao, Guoliang; Li, Lihua
Abstract : Background: Breast tumor heterogeneity is related to risk factors that lead to worse prognosis, yet such heterogeneity has not been well studied. Purpose: To predict the Ki‐67 status of estrogen receptor (ER)‐positive breast cancer patients via analysis of tumor heterogeneity with subgroup identification based on patterns of dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI). Study Type: Retrospective study. Population: Seventy‐seven breast cancer patients with ER‐positive breast cancer were investigated, of whom 51 had low Ki‐67 expression. Field Strength/Sequence: T1 ‐weighted 3.0T DCE‐MR images. Assessment: Each tumor was partitioned into multiple subregions using three methods based on patterns of dynamic enhancement: 1) time to peak (TTP), 2) peak enhancement rate (PER), and 3) kinetic pattern clustering (KPC). In each tumor subregion, 18 texture features were computed. Statistical Testing: Univariate and multivariate logistic regression analyses were performed using a leave‐one‐out‐based cross‐validation (LOOCV) method. The partitioning results were compared with the same feature extraction methods across the whole tumor. Results: In the univariate analysis, the best‐performing feature was the texture statistic of sum variance in the tumor subregion with early TTP for differentiating between patients with high and low Ki‐67 expression (area under the receiver operating characteristic curves, AUC = 0.748). Multivariate analysis showed that features from the tumor subregion associated with early TTP yielded the highest performance (AUC = 0.807) among the subregions for predicting the Ki‐67 status. Among all regions, the tumor area with high PER at a precontrast MR image achieved the highest performance (AUC = 0.722), while the subregion that exhibited the highest overall enhancement rate based on KPC had an AUC of 0.731. These three models based on intratumoral texture analysis significantly ( P < 0.01) outperformed the model using features from the whole tumor (AUC = 0.59). Data Conclusion: Texture analysis of intratumoral heterogeneity has the potential to serve as a valuable clinical marker to enhance the prediction of breast cancer prognosis. Level of Evidence : 4 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2017.